2019
DOI: 10.1038/s41467-019-11911-5
|View full text |Cite
|
Sign up to set email alerts
|

Genetic programming of macrophages to perform anti-tumor functions using targeted mRNA nanocarriers

Abstract: Tumor-associated macrophages (TAMs) usually express an M2 phenotype, which enables them to perform immunosuppressive and tumor-promoting functions. Reprogramming these TAMs toward an M1 phenotype could thwart their pro-cancer activities and unleash anti-tumor immunity, but efforts to accomplish this are nonspecific and elicit systemic inflammation. Here we describe a targeted nanocarrier that can deliver in vitro-transcribed mRNA encoding M1-polarizing transcription factors to reprogram TAMs without causing sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
308
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 356 publications
(339 citation statements)
references
References 69 publications
5
308
0
Order By: Relevance
“…Gene therapy is a unique strategy to polarize TAMs. Zhang et al ( 174 ) describe using in vitro -transcribed mRNA encoding IRF5 and its activating kinase IKKβ encapsulated in nanoparticles to reprogram TAMs in models of ovarian cancer, melanoma, and GBM. The nanoparticles were engineered with D-mannose on the surface to efficiently and specifically target the mannose receptor CD206 + on TAMs.…”
Section: Methods To Prevent Myeloid Cell Contribution To Cancer Growtmentioning
confidence: 99%
“…Gene therapy is a unique strategy to polarize TAMs. Zhang et al ( 174 ) describe using in vitro -transcribed mRNA encoding IRF5 and its activating kinase IKKβ encapsulated in nanoparticles to reprogram TAMs in models of ovarian cancer, melanoma, and GBM. The nanoparticles were engineered with D-mannose on the surface to efficiently and specifically target the mannose receptor CD206 + on TAMs.…”
Section: Methods To Prevent Myeloid Cell Contribution To Cancer Growtmentioning
confidence: 99%
“…Ex vivo treated-TAMs expressed increased levels of cytokines IL-12, IFN-γ, and TNF-α, while IL-6 was decreased. The same treatment was also effective in a murine model of glioma and lung metastasis [132].…”
Section: Rna Delivery To Reprogram Tamsmentioning
confidence: 87%
“…In particular, tumor-associated macrophages (TAMs) are one of the primary biological barriers in cancer tissue invariably encountered by NCs, so that scientists tried to exploit this "disadvantage" using TAMs as a reservoir of nanovehicles, to increase the site-specific drug release [13,77]. Another interesting progress is the design of NCs that can avoid phagocytosis through the modification of their surfaces (e.g., with CD47) [78] or that can modulate the polarization and activity of macrophages [79,80]. In addition, studies about the numerous molecular targets found to develop specific active targeted NCs brought huge knowledge.…”
Section: Is It Still Reasonable To Invest In Cancer Nanomedicine?mentioning
confidence: 99%